Mahomet jako centralna postać wyobrażonej opery w opowiadaniu „Gambara” Balzaca - Gamrat, Małgorzata (Poznańskie Studia Polonistyczne. Seria Literacka, 2022)
The article discusses the fragment of Balzac’s short story Gambara in which the titular character discusses his opera. The focal point of this article is a character from the opera written by Paolo Gambara – Muhammad. The elements used to build the character (character traits, transformations, biography, relationships with his environment, actions, emotions etc.) were analysed in the context of the musical means used to present them and of the entire short story. The background of this analysis consists of a short overview of the philosophical ideas about music and science expressed by Gambara in order to better present the sources of his ideas and the musical solutions that he used.